The lost spells - Macfarlane, Robert, 1976- (House of Anansi Press Inc., 2020)
"Since its publication in 2017, The Lost Words has enchanted readers with its poetry and illustrations of the natural world. Now, The Lost Spells, a book kindred in spirit and tone, continues to re-wild the lives of children and adults. The Lost Spells evokes the wonder of everyday nature, conjuring up red foxes, birch trees, jackdaws, and more in poems and illustrations that flow between the pages and into readers' minds. Robert Macfarlane's spell-poems and Jackie Morris's watercolor illustrations are musical and magical: these are summoning spells, words of recollection, charms of protection. To read The Lost Spells is to see anew the natural world within our grasp and to be reminded of what happens when we allow it to slip away."--